EFFECT OF FOUR WEEK MALARIA AND RBM INITIATIVE EDUCATION AMONG A GROUP OF PREGNANT WOMEN IN ABAKALIKI EBONYI STATE - Omaka, L.N.A (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Malaria is one of the most common and potentially the most serious infection occurring in pregnancy in many sub Saharan African countries. LAck of knowledge about the disease is a common finding in malaria endemic regions like Nigeria and this has been associated to lack of education about malaria. The study examined the effect of four. week malaria education programme on knowledge of a group of pregnant women attending Redeemed Christian church-of God Abakaliki. A total number of sixty-two pregnant women within the period of programme intervention participated in the study. Using the quasi-experimental design, pre-programme and post- programme tests were carried out to determine the impact of the programme on knowledge of malaria with respect to its cause, symptoms, mode of transmission and Roll Back Malaria (RBM) initiative as well as acceptance of Insecticide Treated Bed Net (ITN). Simple percentage was used to analyze data generated from the pre- test and post test respectively. Percentage scores of the post- test programme drastic improvement in the participants' malaria arid RBM knowledge as well as ITN acceptance for malaria prevention during pregnancy compared to the pre-test programme. It was therefore recommended among others that the outcome of the programme suggests the need for the extension of such programme to more churches in the state